IDE411 : 3D modelling and techniques / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
The course is designed to lead the students through the process of model making techniques. The goal of this course is to prepare them for model making techniques with the knowledge and understanding of basic art and design elements and principles. Emphasis is given to problem solving exercises that allow the students to think creatively and critically. This is done through the learning process that stresses the ability of the students to produce model making that shows their understanding of 2 and 3 Dimensional relationship.